Using Panoramic Radiograph for Identification of Mandibular Structures: A Study on Bangladeshi Population (KYAMC Journal, 2020)
Background: Panoramic view of radiograph or Orthopantomogram (OPG) is useful in the aspect of surgery done in mandible, as many visible landmarks can be found in a single tomographic image.Objectives: To evaluate the visibility of anatomical structures of mandible in OPG and to determine the relationship of age and gender with this.Materials and Methods: It was a cross-sectional study and was conducted in dental OPD of Noakhali General Hospital from January 2019 to June 2019, six-month period. Data were analyzed by SPSS version 20.Results: A Total of 272 OPGs were examined of patients (female 165, male107), having age range of 7-90 years. Here highest visible structure was mandibular canal (about 97.4%) followed by mental foramen and mandibular foramen, where visibility was 92.3% and 87.5% respectively. Anterior loop of mental nerve and incisive canal were seen in 33.5% and 31.6% cases respectively. Only in 15.1% OPG, lingual foramen was visible. There is no significant relationship between gender and visibility of structures (p>0.05). Age and visibility of landmarks showed significant relation only in case of mental foramen and mandibular canal (p